Implementasi Metode TOPSIS Sebagai Pendukung Keputusan Penentuan Guru Teladan Di SMK Grafika Gadingrejo - Anggraeny, Yanike Anestasya; Suprapto, Bambang (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
Model teachers are one way to improve school quality. All components in the learning process in schools, the development of the learning process without the support of the presence of professional teachers, schools will not improve. Determination of an exemplary teacher must be done in every school, especially in SMK Grafika Gadingrejo. The problem is how to determine an exemplary teacher with a variety of factors with which to and diverse criteria. To simplify the assessment process, a decision support system is needed to determine the exemplary teacher with a decision support system with the TOPSIS (Technique for Others Reference by Similarity to Ideal Solution) method. TOPSIS method is a method with a simple concept that is easy to understand, and can solve multi-criteria problems by calculating the values of existing criteria. Based on the results of these case examples show that the results of jewelry use the same system with manual calculations. The calculation of the Topsis Method will produce an output in the form of ranking.